Problems in property tax collection: A case study in Majlis Daerah Kulai / Mohamad Zahren Sahar - Sahar, Mohamad Zahren (Faculty of Business Management, 2002)
Property tax is one of the main sources of revenue for all Local Authority Parties including the Majlis Daerah Kulai (MDK). However, to collect this property tax revenue has always been a difficult task to MDK. It has been facing with several problems and barriers in gaining property tax either On the property, which can be collected but not collected yet or on the property, which can be collected but involving arrears. This study was conducted to uncover the problems in the property tax collections at Majlis Daerah Kulai (MDK), to identify the contributing factors towards the problems and to provide possible recommendations, which could help MDK maximise its property tax collections. The MDK has experienced a significant loss in its revenue needed to fund the development in its areas. For the purpose of this study, a total of 50 questionnaires have been distributed to the respondents representing all property holders in Kulai area. Besides, personal interviews and observations with selective MDK staff and residents of Kulai have also been performed. The data collected from the questionnaires, interviews and observations have then been analyzed to get the information needed regarding the problems occur. The findings had revealed two major factors, which significantly contributed to the problems in the property tax collections. First, it was the people's attitudes towards their own responsibilities to pay tax and lastly the quality of services rendered by the MDK. Majority of the residents were able to pay the tax but some chose not to pay regardless of the standard of services provided by the MDK. On the other hand, there were residents who refused to pay the tax just because they believed that MDK did not provide satisfactory services to them. MDK was recommended to take necessary actions immediately to prevent the problems from deteriorating, which could significantly have a great impact on the collections of the property tax. The most significant action was for the MDK to increase its revenue and this could possibly be achieved with proper management in terms of planning, strategies and implementation. Besides, it was equally important to increase the ability and performance of its enforcement staff and to upgrade the quality of the services rendered to the peoples in its areas. Nevertheless, it was hoped that the basic findings revealed in this study could provide MDK with a better understanding of their internal and external problems and the needs to inculcate the residents in its areas of their responsibility to pay the property tax.